A manager's guide to ISO22301 a practical guide to developing and implementing a business continuity management system - Drewitt, Tony (IT Governance Pub., 2013)
A concise and practical guide to the ISO22301 benchmark for business continuity management. Essential reading for all managers, executives and directors with any interest or involvement in operational risk or business continuity management.